Nursing care in neonatal sepsis (Research, Society and Development, 2021)
Neonatal sepsis is a severe systemic inflammatory syndrome resulting from infection with or without bacteremia that can occur through positive culture in the first 28 days of life. The involvement of neonatal sepsis is responsible for five million deaths of newborns in underdeveloped or developing countries. Thus, the objective of the study is to discuss the contribution of nursing care to reduce the rate of neonatal sepsis. It is known that nursing has a very important role in monitoring children in the NICU, a practice based on theoretical-methodological knowledge in addition to the Systematization of Nursing Care-SAE, which is a methodology that provides security to nursing practice. The study sought to present a literature review on nursing care in assisting children in the ICU with neonatal sepsis, reinforcing the importance of early diagnosis and treatment intervention. The research presents the clinical concept of neonatal sepsis, its clinical characteristics and nursing care for the care of newborns with this infection. This is a bibliographic research of descriptive character with a qualitative approach using scientific articles published in the databases, Lilacs, Scielo, Medline, among other journals and the legal regulations of the Ministry of Health that address the subject. The study highlights the importance of preventive care in newborn care, adopting preventive measures and recognizing early signs to treat neonatal sepsis, thus reversing the consequences of the infection.